2019
DOI: 10.1111/sms.13470
|View full text |Cite
|
Sign up to set email alerts
|

Re‐examination of accelerometer data processing and calibration for the assessment of physical activity intensity

Abstract: This review re‐examines the use of accelerometer and oxygen uptake data for the assessment of activity intensity. Accelerometers capture mechanical work, while oxygen uptake captures the energy cost of this work. Frequency filtering needs to be considered when processing acceleration data. A too restrictive filter attenuates the acceleration signal for walking and, to a higher degree, for running. This measurement error affects shorter (children) more than taller (adults) individuals due to their higher moveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 53 publications
(241 reference statements)
0
28
0
Order By: Relevance
“…The high variability of cut-off frequencies is justified by the variety of parameters extracted by the authors of the papers, and the locations of the sensors on the human body. It has been shown that low cut-off frequencies attenuate inertial sensor signals, while less restrictive filtering may provide more movement-related signals, but with the risk of higher noise [75]. Future studies should include more technical details regarding pre-processing of raw data used to calculate gait metrics, justifying their choices in light of existing literature.…”
Section: Discussionmentioning
confidence: 99%
“…The high variability of cut-off frequencies is justified by the variety of parameters extracted by the authors of the papers, and the locations of the sensors on the human body. It has been shown that low cut-off frequencies attenuate inertial sensor signals, while less restrictive filtering may provide more movement-related signals, but with the risk of higher noise [75]. Future studies should include more technical details regarding pre-processing of raw data used to calculate gait metrics, justifying their choices in light of existing literature.…”
Section: Discussionmentioning
confidence: 99%
“…The subjects were divided into a preschool group (5-6 years, N = 29), a child group (9-11 years, N = 35), an adolescent group (14-16 years, N = 31), and an adult group (> 18 years, N = 38). Identifying age-independent MPA and VPA intensity-specific counts thresholds is challenging, and adjusting for basal metabolic rate to account for body weight, height, and maturation is not an accurate solution [30]. The metabolic and mechanical cost of walking at self-selected speed is similar across a large age range [31] and performed at an intensity corresponding to 30-35% of individuals' VO 2max .…”
Section: Data Reduction Of Raw Accelerometer Datamentioning
confidence: 99%
“…Advertisements in electronic media, social networks, and leaflets were used to recruit the participants of the study. Exclusion criteria were: being physically active (more than 20 min of moderate-vigorous physical activity on more than 3 d/week) [25], being participants of a structured exercise intervention during the last 3 months, presenting a non-stable body weight (i.e., >3 kg) during the previous 3 months, being smokers, suffering from cardiometabolic disease, and/or being pregnant. The baseline assessment of the participants of the FIT-AGEING study was conducted during September (2016 and 2017) in the Sport and Health Joint University Institute (iMUDS, Granada, Spain).…”
Section: Design and Participantsmentioning
confidence: 99%